2016
DOI: 10.4196/kjpp.2016.20.2.201
|View full text |Cite
|
Sign up to set email alerts
|

NecroX-5 protects mitochondrial oxidative phosphorylation capacity and preserves PGC1α expression levels during hypoxia/reoxygenation injury

Abstract: Although the antioxidant and cardioprotective effects of NecroX-5 on various in vitro and in vivo models have been demonstrated, the action of this compound on the mitochondrial oxidative phosphorylation system remains unclear. Here we verify the role of NecroX-5 in protecting mitochondrial oxidative phosphorylation capacity during hypoxia-reoxygenation (HR). Necrox-5 treatment (10 µM) and non-treatment were employed on isolated rat hearts during hypoxia/reoxygenation treatment using an ex vivo Langendorff sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…Our previous proteomics study and network analysis [ 35 ] revealed a small protein network that comprised three identified proteins (Dcn, collagen alpha-2[I] chain [Col1a2], and lumican [Lum]) and two predicted networking proteins (TGFβ1 and SMAD2; Fig. 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous proteomics study and network analysis [ 35 ] revealed a small protein network that comprised three identified proteins (Dcn, collagen alpha-2[I] chain [Col1a2], and lumican [Lum]) and two predicted networking proteins (TGFβ1 and SMAD2; Fig. 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…LC-MS and a non-labeled peptide count protein quantification method were used to analyze the proteomes of rat hearts as described previously [ 35 36 ]. Heart proteins were separated via SDS-PAGE on a 12% polyacrylamide gel.…”
Section: Methodsmentioning
confidence: 99%
“…IRE1a deficiency suppressed the ability of MRSA-infected macrophages to induce mH 2 O 2 compared to the non-targeted control (Figure 1E). To test the requirement for mROS in killing MRSA, we treated infected macrophages with the ROS scavenger NecroX-5, which is primarily localized to mitochondria (Kim et al, 2010;Thu et al, 2016). Infected macrophages treated with NecroX-5 exhibited significantly lower MitoPY1 fluorescence than control-treated cells ( Figure 1F) and decreased capacity to kill MRSA ( Figure 1G).…”
Section: Induction Of Mros By Ire1a Promotes Macrophage Bactericidal mentioning
confidence: 99%
“…1E). To test the requirement for mROS in killing MRSA, infected macrophages were treated with the ROS scavenger, NecroX-5, which is primarily localized to mitochondria (Kim et al, 2010; Thu et al, 2016). Infected macrophages treated with NecroX-5 exhibited lower MitoPY1 fluorescence than control-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 99%